2016
DOI: 10.1016/j.memsci.2015.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and membrane stability study for the switchable polarity solvent N,N-dimethylcyclohexylamine as a draw solute in forward osmosis

Abstract: Commercially available reverse osmosis and forward osmosis thin-film composite membranes were assessed for long-term chemical stability when immersed in 10 molal N,N-dimethylcyclohexylammonium hydrogen carbonate draw solution, a model switchable polarity solvent draw solute for forward osmosis. Membrane performance was monitored with reverse osmosis testing, including rejection of 2000 ppm sodium chloride (NaCl), for three commercial reverse osmosis membranes-Dow BW30, SW30HR, and SW30HR with polyester backing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…heating [22] 1--Cyclohexylpiperidine (CHP) heating [23] Organic compounds Micellar solution UF [24] oxalic acid complexes with Fe/Cr/Na nanofiltration (NF) [25] trimethylamine-carbon dioxide heating [26] CO2-responsive polymers (PDMAEMA) UF [27] poly(sodium styrene-4-sulfonate-co-Nisopropylacrylamide) (PSSS-PNIPAM) MD [28] Switchable polarity solvent (SPS) RO [29] polyelectrolyte incorporated with triton-x114 MD [30] dimethyl ether heating with solar energy [31] poly(4-styrenesulfonic acid-co-maleic acid) NF [32] Super hydrophilic nanoparticles UF [33] hydrophilic superparamagnetic nanoparticles magnetic separation [34] Functional nanoparticles magnetic core-hydrophilic shell nanosphere magnetic separation [35] thermoresponsive Magnetic Nanoparticle magnetic separation [36] dextran-coated MNPs magnetic separation magnetic separation [37] hyperbranched polyglycerol coated MNPs magnetic separation [38] In addition to fouling of membrane, concentration polarization has an impact on the water flux, particularly at the support layer, which leads to the severity in internal concentration polarization (ICP). A low ICP requires a low S-value (structural parameter) [43,77].…”
Section: Categoriesmentioning
confidence: 99%
“…heating [22] 1--Cyclohexylpiperidine (CHP) heating [23] Organic compounds Micellar solution UF [24] oxalic acid complexes with Fe/Cr/Na nanofiltration (NF) [25] trimethylamine-carbon dioxide heating [26] CO2-responsive polymers (PDMAEMA) UF [27] poly(sodium styrene-4-sulfonate-co-Nisopropylacrylamide) (PSSS-PNIPAM) MD [28] Switchable polarity solvent (SPS) RO [29] polyelectrolyte incorporated with triton-x114 MD [30] dimethyl ether heating with solar energy [31] poly(4-styrenesulfonic acid-co-maleic acid) NF [32] Super hydrophilic nanoparticles UF [33] hydrophilic superparamagnetic nanoparticles magnetic separation [34] Functional nanoparticles magnetic core-hydrophilic shell nanosphere magnetic separation [35] thermoresponsive Magnetic Nanoparticle magnetic separation [36] dextran-coated MNPs magnetic separation magnetic separation [37] hyperbranched polyglycerol coated MNPs magnetic separation [38] In addition to fouling of membrane, concentration polarization has an impact on the water flux, particularly at the support layer, which leads to the severity in internal concentration polarization (ICP). A low ICP requires a low S-value (structural parameter) [43,77].…”
Section: Categoriesmentioning
confidence: 99%
“…NaCl reverse osmosis (RO) [33] inorganic fertilizer direct use [45] potassium sulfate (K 2 SO 4 ) RO [33] sodium nitrate (NaNO 3 ) direct use [46] aluminum sulfate (Al 2 (SO 4 ) 3 ) precipitation [47] magnesium sulfate (MgSO 4 ), copper sulfate (CuSO 4 ) precipitation [48,49] Organic compounds Switchable polarity solvent (SPS) RO [50] sodium polyacrylate (PAA-Na) ultrafiltration (UF), membrane distillation (MD) [51,52] CO 2 -responsive polymers (PDMAEMA) UF [53] poly(sodium styrene-4-sulfonate-co-N-isopropylacrylamide) (PSSS-PNIPAM) MD [54] poly (aspartic acid sodium salt) MD [55] N,N-dimethylcyclohexylamine (N(Me) 2 Cy) heating [56] 1-Cyclohexylpiperidine (CHP) heating [57] Micellar solution UF [58] oxalic acid complexes with Fe/Cr/Na nanofiltration (NF) [59] 2-Methylimidazole compounds MD [60] trimethylamine-carbon dioxide heating [61] glucose, fructose RO [62][63][64] polyelectrolyte incorporated with triton-x114 MD [65] dimethyl ether heating with solar energy [66] poly(4-styrenesulfonic acid-co-maleic acid) NF [67] Functional nanoparticles…”
Section: Inorganic Compoundsmentioning
confidence: 99%
“…Besides, the removal of the trace amounts of ammonia in product water is still a big challenge. Later, to overcome the mentioned defects above, a series of ammonium carbonate salts with similar function of NH 3 -CO 2 , such as N,N-dimethylcyclohexylamine (N(Me) 2 Cy) [56], 1-Cyclohexylpiperidine (CHP) [57], trimethylamine (N(CH 3 ) 2 ) [61] and switching polarity solution (SPS) [50] have been reported.…”
Section: Gas and Volatile Compoundsmentioning
confidence: 99%
“…In addition to extracting lipids from soybeans, SHSs have been used to isolate lipids from algae, [5][6][7][8] bitumen from oil sands, 9,10 and phenols from lignin pyrolysis oil. 11 Interest has also been shown in applying SHSs to other applications such as water purication, [12][13][14][15][16][17][18] microextraction for detecting and quantifying environmental contaminants, [19][20][21][22][23][24][25] separations of reaction products from organocatalysts, 26 emulsion formation, 27 and processing recyclable materials. 3,28 Previous studies showed that monoamine SHSs can be largely separated from dissolved products by the action of carbonated water, but some solvents might not be sufficiently removed from the product because the partitioning of the SHS into the aqueous phase was inadequate.…”
Section: Introductionmentioning
confidence: 99%